HUBUNGAN ANTARA DUKUNGAN SOSIAL PASANGAN DENGAN KETERIKATAN KERJA PADA APARAT PEMERINTAH DESA DI KECAMATAN X,Y,Z KABUPATEN BATANG - SEPTIANI, NURALINA; Nurtjahjanti, Harlina (Empati, 2017)
Work engagement is a positive attitude belonged by someone toward his occupation. It can be identified by looking at the high vigor, fully dedication and focus orientation as well as the love toward his job which enable him blended with his work. Social support of spouse is an individual perception of support given by spouse (might be wife or husband) to make someone feels regarded, appreciated, and loved. This research is intended to reveal the correlation between social support given by spouse and work engagement within the village government apparatus in X,Y,Z districts, Batang regency. The populations of this inquiry consist of 237 married village government apparatus in X,Y,Z districts, Batang regency. Furthermore, the data obtained by convenience sampling technique with 101 of total subjects. The research instrument is comprised of two scales that is work engagement scale (36 aitem Î± ; = 0,926) and the scale of social support of spouse (31 aitem Î± ; = 0,920), while the data analysis of this inquiry applied the simple regression analysis. The finding of this research indicates the positive correlation between social support given by spouse and work engagement within the village government apparatus in X,Y,Z districts, Batang regency (rxy= 0,665), social support of spouse gives the effective contribution in 44,2%.Â